Erratum to “Character and Adab Education in Indonesia, Turkey, and Japan: A Comparative Study” [Islamic Guidance and Counseling Journal 6(1) 2023] - Syamsul Huda; Nilawati Tadjuddin; Ahmad Sholihuddin; Korhan Cengiz (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
Refers to: Huda, S., Tadjuddin, N., Sholihuddin, A., Kato, H., & Cengiz, K. (2022). Character and Adab Education in Indonesia, Turkey, and Japan: A Comparative Study. Islamic Guidance and Counseling Journal, 6(1), 1–17. https://doi.org/10.25217/igcj.v6i1.2973 Erratum:In the original published version of this article, the authors listed were Syamsul Huda, Nilawati Tadjuddin, Ahmad Sholihuddin, Hisanori Kato, and Korhan Cengiz. However, on September 4, 2023, Hisanori Kato from Chuo University, Japan, reached out to the Editorial Team. He clarified that he had never participated in the research and had not consented to be named as a co-author. Consequently, he requested an investigation and removal of his name from the author list. After consulting to the journal’s policy and COPE guidelines (https://publicationethics.org/retraction-guidelines), the list of authors has been updated. Hisanori Kato from Chuo University, Japan has been removed from the co-authors list.